Internalisasi Nilai-Nilai Moderasi Beragama pada Masyarakat Multikultural di Desa Bantengan, Kec. Wungu Kab. Madiun - Khoirotus Sa’diyah; Widya Astuti Sari; Linda Dwi Novita Wardani; Siti Nur Hasanah (Pusat Riset dan Inovasi Nasional, 2025)
Indonesia is a unitary state, has a lot of diversity that combines various nationalities, dialects, religions, and communities. Therefore, as a diverse nation, moderation in religion is needed so that there is no degenerate behavior that can divide a country. Internalization of religious values in a multicultural society is an effort to integrate religious values with cultural and religious diversity in society. The main purpose of this internalization is to increase tolerance, respect diversity, and form an inclusive religious culture. This study aims to discuss the internalization of religious moderation values in a multicultural society. This study uses a qualitative approach and data processing using descriptive-analytical methods. Data processing is used as a benchmark to find out how the internalization of religious moderation values in a multicultural society, then takes several sources from the Bantengan village community to be used as research objects, in order to answer the main research questions, including: 1) How is the process of conveying understanding the values of religious moderation in a multicultural society in Bantengan Village. 2) How is the negotiation process with the community regarding the values of religious moderation in a multicultural society in Bantengan Village. 3) -How is the implementation of the values of religious moderation in a multicultural society in Bantengan Village? From the results and discussion of this study, it shows that there are several ways that the Bantengan village community does to internalize the values of religious moderation in a multicultural society. This study concludes that internalization of the values of religious moderation in a multicultural society in Bantengan Village can be done in various ways. An important effort to internalize the values of religious moderation in a multicultural society is to make the Bantengan village community a harmonious society by strengthening tolerance between religious communities, and having a spirit of justice between communities.